171 ORPHANIN FQ/NOCICEPTIN REGULATION OF STERIOD ACTIVATION OF μ-OPIOID RECEPTORS AND SEXUAL BEHAVIOR IN RAT MODELS. (1st January 2006) - Nguyen, Y.; Sinchak, K.; Dewing, P.; Micevych, P.
Abstract : Previous studies have shown that estrogen and progesterone play an important role in facilitating sexual receptivity by regulating the activity of the μ-opioid receptor (MOR) in the medial preoptic nucleus (MPN) and the opioid receptor like receptor (ORL-1) in the ventral medial hypothalamus (VMH). Estrogen rapidly activates MOR in the MPN via the release of β-endorphin originating from neurons in the arcuate, which inhibit lordosis. Subsequent progesterone facilitates lordosis by activating ORL-1 through the release of OFQ/N into the VMH or ARH. Since the ARH projects into the MPN, we hypothesize that infusion of orphanin FQ/nociceptin (OFQ/N) exogenous ligand into the VMH-ARH region will facilitate lordosis by attenuating the activity of MOR inhibitory circuit. Secondly, we will test whether OFQ/N is the endogenous ligand acting in the VMN-ARH region to facilitate lordosis. To test whether OFQ/N activation in the VMH-ARH blocks MOR activity in the MPN and facilitates lordosis, two groups of estrogen primed, nonreceptive ovariectomized rats were either implanted with bilateral cannula aimed at the VMH or a unilateral cannulae aimed at the ARH, using standard stereotaxic procedures. The VMH group was infused with either anti-OFQ (Phoenix 1:10, Neuromics 1:2) to passively immunoneutralize endogenous OFQ/N or normal rabbit serum as control 48 hours post 5 μg estradiol benzoate injection and tested 10 and 90 minutes later to measure sexual receptivity, as measured by lordosis quotient. One week after the behavioral experiment, these animals and the unilateral ARH cannulated animals were treated with 2 μg estrogen and 30 hours later infused with either 25 nmol OFQ/N or artifical cerebrospinal fluid (aCSF). Thirty minutes later, both groups were perfused transcardially with paraformaldehyde and the MPN of each animal was processed for MOR immunohistochemistry. The level of MOR internalization, a marker for receptor activation, was measured by density of immunoreactivity. Immunoneutralization of OFQ/N in the VMH blocked the facilitation of lordosis, indicating that OFQ/N is a relevant ligand in the facilitation of lordosis in the VMH (ANOVA, p < .05). Furthermore, microinfusion of OFQ/N ligand into the VMH and ARH decreased MOR immunoreactivity density in the MPN compared to aCSF controls. These experiments together indicated that estrogen and progesterone facilitation of sexual receptivity involves OFQ/N acting via ORL-1 receptors in the VMH/ARH that subsequently attenuate the MOR inhibition in the MPN by preventing the release of β-endorphins from neurons in the ARH.